PAX 2 Mutation in an Indian Family with Renal Coloboma Syndrome - Kumar Digvijay; Grazia Maria Virzì; Diego Pomarè Montin; Lucas Gobetti da Luz; Maryam Momeni Taramsari; Ashwani Gupta; Manish Malik; Anurag Gupta; Vinant Bhargava; Meenakshi Verma; Claudio Ronco; Devinder Singh Rana; et al. (2023)
The transcription factor encoded by the PAX2 gene plays a significant role in the development of the urogenital tract, eyes, ears, and central nervous system. Heterozygous mutations in the PAX2 gene cause renal coloboma syndrome, a rare autosomal dominant disorder characterized by optic nerve coloboma and renal anomalies. In this study, two siblings with chronic kidney disease (CKD) receiving regular dialysis therapy were investigated. DNA sequencing was performed on blood samples from both patients, which revealed four novel heterozygous variations in the PAX2 gene in both patients. Sequencing analysis showed a C to G transversion at position c.352 of the PAX2 gene in a heterozygous state.